"Effect of Soil moisture content and tillage depth on tractor performance with using moldboard plow in silty-clay soil" - Khorshid, Fawzy F. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The experiment was conducted in the field of Faculty of agriculture science / sulaimani University in 2012 – 2013 to study the Effect of Soil moisture content and tillage depth on tractor performance with using moldboard plow in silty-clay soil. Split plot design and randomized complete block design (RCBD) was used in this study. Two factors including two tillage depth levels 15 and 25 cm represent the main plot and three soil water content including 10, 15 and 20 % represent sub plot were used in this study . Fuel consumption, Practical speed, Tire slippage, Tillage soil volume, Soil penetration resistance, Porosity and No. Of soil clods that larger than 10 cm where studded. The study shows that: - Significant differences were observed between the two tillage depth treatment means, water content treatment means, and them interaction means for all studied characters in the experiment. also the study shows the best results for all the characters was for the treatment of depth 15 cm compared to the depth of 25 cm, while the opposite happened for the tillage soil volume where the depth 25 cm Superiority on 15 cm depth by giving him the highest value. as for water content factor, the value for fuel consumption, practical speed, tire slippage, and tillage soil volume increased Significantly with increasing soil water content from 10 to 15 then to 20%, while the values for other characters decreased. Also There were differences among the interaction treatment means for all characters value in the experiment that most of them where significant.
Keywords: Soil MoistureTillage DepthMechanical PropertiesSoil Physical PropertiesTriple Mold Board Plow